VEGETATION CHANGES ANALYSIS USING NDVI (NORMALIZED DIFFERENCE VEGETATION INDEX) METHOD IN KALIANDA SUBDISTRICT, LAMPUNG SELATAN DISTRICT, INDONESIA - Winih Sekaringtyas Ramadhani; Ali Rahmat; Asha Ananda Arza (The Republic of Indonesia Defense University, 2021)
Each year, the population in Kalianda subdistrict, Lampung province keeps increasing. The increase in population means that the need for living space also increasing, this can lead to land cover conversion from a vegetation area to a residential area. To find how much the change in land conversion over the year, a spatial analysis over the period of 18 years was needed. So that it is expected to be able to manage spatial planning to cope with disasters in Indonesia. This research uses Landsat 7 and 8 images that have been calculated using the Normalized Difference Vegetation Index (NDVI) method. The results show that between 2010 - 2019, there is an increase in land cover changes in open land/house/building/no vegetation around 814 ha (6.9%), in low vegetation increase 975 ha (8.4%). However, in the medium vegetation was decreasing around 1123 ha (9.5%). Overall observation sample of the ground check is following the actual condition of land cover in Kalianda Sub-district. The data show that in the Kalianda subdistrict, land management is necessary to suppress land cover changes so that it won’t lead to environmental disasters